A Konstribusi Intelektual Muhammad Nejatullah Siddiqi dalam Dinamika Pemikiran Ekonomi Islam Kontemporer - Faizah adawiyah; meylandria Early; Agus Waluyo (Sekolah Tinggi Ilmu Ekonomi Syariah Nahdlatul Ulama Bengkulu, 2026)
This study aims to outline the biography and academic contributions—in the form of ideas and works—of Muhammad Nejatullah Siddiqi in addressing contemporary economic challenges. This study employs a literature review (library research) method using a descriptive-analytical approach by examining various sources of literature, including books, scientific journals, and related articles. The findings indicate that Siddiqi successfully integrates Western neoclassical-Keynesian economic theory with Islamic jurisprudence (fiqh) and Islamic values rooted in the Qur’an and Sunnah. His core ideas encompass ensuring individuals’ basic needs through five institutional foundations, a production and distribution system for the public good, and the optimization of zakat as an instrument of national fiscal policy. Additionally, Siddiqi proposes the profit-sharing mechanism (mudharabah) as an alternative to the exploitative conventional banking interest system, which involves usury. His ideas have proven to be applicable and relevant to the Islamic economic ecosystem in Indonesia, as seen in BAZNAS’s social safety net programs, the growth of Islamic cooperatives, and the operations of local Islamic banking products that prioritize fairness for economic actors.